Intermolecular insertion of dialkynylphosphanes into the M–C bond of cyclopalladated rings through activation by cyclometallated amines - Chen, Shuli (2013)
A series of chiral ortho-platinated and -palladated complexes derived from N,N,α-trimethylbenzylamine has been prepared. The dialkynylphosphane PhP(C CMe)2 coordinated regiospecifically as a P M monodentate ligand to these cyclometallated units in the positions trans to the nitrogen donors of the metallacycles. Upon introduction of selected chirality on the benzylamine unit and subsequent monitoring by using NMR spectroscopy, the P Pt bond was found to be thermodynamically stable and kinetically inert. The P Pd bond must be kinetically labile since the palladium complexes readily undergo a facile ligand redistribution process. Nevertheless, both ortho-metallated units activated one of the C C bonds towards an intermolecular Pd–C bond insertion reaction into another cyclopalladated ring. No intramolecular insertion reaction occurred within the same molecule. Coordination of PhP(C CMe)2 to the ortho-palladated unit also protected the organopalladium ring from intermolecular attack by other coordinated dialkynylphosphanes. The Pt–C bonds in cycloplatinated rings are not reactive toward the insertion reaction, although they are good reaction activators for coordinated dialkynylphosphanes.